Synergetic Light-Harvesting and Near-Field Enhancement in Multiscale Patterned Gold Substrates - Hernandez, Luis Alfonso Guerra (2015)
Sphere-segment void (SSV) cavities have emerged as promising substrates for reproducible Surface Enhanced Raman Scattering (SERS), offering strong and uniform electromagnetic enhancement associated with the excitation of cavity-like localized surface plasmon resonances tunable across the UV–vis-near IR range, with a facile large-scale fabrication process. High-resolution electron micrographs of these structures reveal a considerable departure from the idealized smooth spherical cavity shape; notably, the electrochemical deposition of gold yields an important surface roughness. We investigate this contribution to the SERS activity of SSV substrates with a series of experiments, varying the degree of surface roughness using thermal annealing and gradual electrochemical roughening. Notably, we observe that both roughness features and cavity-like modes operate in conjunction as a multiscale antenna to provide larger SERS efficiency than the two mechanisms considered separately. We conclude that the main role of the ordered cavity structure is to increase the plasmonic mode density near rough surface features, thus optimizing the coupling of far-field radiation (light harvesting) to locally enhanced near fields.